The prefix g- and -o- ablaut in Tibetan present verb stems - Hill, Nathan (My University, 2020)
The prevailing internal reconstruction of the Classical Tibetan verbal system accounts for all ablaut phenomena as innovations triggered by erstwhile segmental affixes. The traditional account cannot be correct, because the paradigms of nine verbs show -o- in the present stem without g- and a further three verbs show g- in the present without -o-. 1
PUBLISHED
Keywords: Tibetan verb; ablaut; verb morphology; Tibeto-Burman